Etika Profesi dalam Perspektif Hukum: Tantangan dan Implementasi - Eka Kusuma, Dian (Sawerigading Law Journal, 2024)
Professional ethics are the moral foundation that underlies the behavior and responsibilities of a professional in carrying out his/her duties. In the legal field, the application of professional ethics has a strategic role in maintaining integrity, justice, and public trust in the legal profession. This article aims to analyze the concept of professional ethics in the legal realm and the challenges faced in its implementation in Indonesia. This study uses a normative juridical method with a conceptual approach and case study analysis. The results of the study show that although there have been clear regulations regarding the code of ethics of the legal profession, there are still violations caused by lack of supervision, conflicts of interest, and weak sanctions. To overcome this problem, strengthening regulations, stricter supervision, and ongoing ethics education are needed.